1984
DOI: 10.1192/bjp.144.1.35
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Study of Emotional Disorders in Childbearing Women

Abstract: A group of first-time mothers (119) were interviewed repeatedly at fixed intervals during their pregnancies and until their babies were a year old; they were then followed up at four years. A similar investigation was carried out on 38 other primiparae and 39 multiparae, but only postnatally. The incidence of depressive neurosis rose significantly in early pregnancy and in the first three months after delivery (10 per cent and 14 per cent of the main sample respectively). Subjects mainly suffered either from a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

45
416
6
38

Year Published

1996
1996
2009
2009

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 875 publications
(505 citation statements)
references
References 21 publications
45
416
6
38
Order By: Relevance
“…With the exception of maternal perceptions of paternal investment, all important correlates of PPD are supported, at least in part, by objective measures, including hospital charts, researcher ratings of mother-infant interactions, face-to-face interviews and observations, income levels, and unemployment status Campbell et al 1992;Hopkins et al 1987;Kumar and Robson 1984;O'Hara et al 1984;Paykel et al 1980;Warner et al 1996;Whiffen and Gotlib 1989). The validity of the paternal investment data is supported by longitudinal studies where the maternal perception of paternal support was collected prepartum when the mothers were not depressed (Gotlib et al 1991) and where the father's mood (assessed by the father's self-report) predicted the mother's future mood (assessed by the mother's self-report).…”
Section: Self-report Methodologiesmentioning
confidence: 99%
See 3 more Smart Citations
“…With the exception of maternal perceptions of paternal investment, all important correlates of PPD are supported, at least in part, by objective measures, including hospital charts, researcher ratings of mother-infant interactions, face-to-face interviews and observations, income levels, and unemployment status Campbell et al 1992;Hopkins et al 1987;Kumar and Robson 1984;O'Hara et al 1984;Paykel et al 1980;Warner et al 1996;Whiffen and Gotlib 1989). The validity of the paternal investment data is supported by longitudinal studies where the maternal perception of paternal support was collected prepartum when the mothers were not depressed (Gotlib et al 1991) and where the father's mood (assessed by the father's self-report) predicted the mother's future mood (assessed by the mother's self-report).…”
Section: Self-report Methodologiesmentioning
confidence: 99%
“…Similarly, Campbell et al (1992) found that not being happy about the pregnancy distinguished women with PPD from those without. Finally, Kumar and Robson (1984) found that women with PPD had significantly more often considered an abortion.…”
Section: The Defection Hypothesis Part Two: Reduce Costsmentioning
confidence: 99%
See 2 more Smart Citations
“…Os três primeiros meses após o parto são particularmente importantes em relação a qualquer outra etapa de vida da mulher, pois nessa fase ela apresenta a maior taxa de risco de internação decorrente de um transtorno psiquiátrico (5) .…”
Section: Introductionunclassified